Pelatihan Pelatih Cabang Olahraga Pencak Silat Kalimantan Timur - Nanda Alfian Mahardhika; Jeane Betty Kurnia Jusuf; Januar Abdilah Santoso; Galih Priyambada; Julianur; M Riski Adi Wijaya (Journal of Empowerment and Community Service (JECSR), 2022)
This community service aims to develop the human resources of pencak silat trainers in East Kalimantan Province by increasing their understanding of coaching theory and their ability to plan training programmes. This service activity is carried out in collaboration with the East Kalimantan IPSI. The trainees totaled 93 pencak silat trainers used lectures, discussions, and practise methods over the course of two days. The outcomes of this service activity include the following: (1) establishment of cooperation between the FKIP UMKT Sports Education Study Program and the IPSI of East Kalimantan Province; (2) enhancement of human resources and trainers' competence in areas such as coaching knowledge and training programme design; and (3) implementation of community service programmes. The service concludes that collaboration and collaboration between the Sports Education Study Program FKIP UMKT and the IPSI in East Kalimantan is a strategic step toward improving human resources and the competence of pencak silat trainers in sport science-based sports coaching theory. This collaboration between agencies can be expanded to include the implementation of additional programmes aimed at increasing the human resources and competence of pencak silat trainers in East Kalimantan